2006
DOI: 10.1111/j.1745-7254.2006.00352.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolic acid inhibits SLE-associated cytokine expression and promotes apoptosis of peripheral blood mononuclear cells from patients with systemic lupus erythematosus1

Abstract: Aim: To investigate the effect of the novel immunosuppressant mycophenolic acid (MPA) on cytokine production and apoptosis of the peripheral blood mono‐nuclear cells (PBMC) of patients with systemic lupus erythematosus (SLE). Methods: The levels of IL‐10, IL‐12, IFN‐γ, sFas and sFasL in the supernatants of cultured PBMC from 41 SLE patients was determined by the ABC‐ELISA method. The percentage of IFN‐γ+IL‐10−, IFN‐γ−IL‐10+, and IFN‐γ+IL‐10+ subsets in CD4+ cells were detected by three‐color flow cytometry. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Finally, because our SLE patients were receiving different treatments and some drugs such as antimalarials (38–40) or immunosuppressive agents (41) have been reported to influence cytokine production, we investigated if the cytokine imbalance observed in our patients might be associated with the treatment they were receiving. No differences were found both in the soluble cytokine levels and in the intracellular expression in T lymphocytes among all groups when considering all treatments the patients were receiving, although, because a small number of patients were included in each group, more studies are needed to confirm these preliminary results and to clarify the influence of treatment on the cytokine production in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, because our SLE patients were receiving different treatments and some drugs such as antimalarials (38–40) or immunosuppressive agents (41) have been reported to influence cytokine production, we investigated if the cytokine imbalance observed in our patients might be associated with the treatment they were receiving. No differences were found both in the soluble cytokine levels and in the intracellular expression in T lymphocytes among all groups when considering all treatments the patients were receiving, although, because a small number of patients were included in each group, more studies are needed to confirm these preliminary results and to clarify the influence of treatment on the cytokine production in SLE.…”
Section: Discussionmentioning
confidence: 99%
“…The disease occurs in young women of childbearing age and the prevalence of females accounts for 90% of the total number of affected patients. The peak age of the disease is 15–40 years (3,4). SLE usually affects the whole body, and there are multiple autoantibodies in the patient's serum as clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] These improvements are more likely due to MMF and not to prednisolone as the daily dose of the steroid decreased significantly with MMF administration. A possible mechanism for MPA's effect in SLE, as suggested by Su et al, 24 is the modulation of cytokine expression (interleukin-10 and interleukin-12 and interferon-c) by MPA. Jiang et al 25 reported that enhanced interleukin-10 promoted B-cell proliferation and differentiation and stimulated the production of pathogenic anti-DNA antibody.…”
Section: Discussionmentioning
confidence: 98%
“…A possible mechanism for MPA’s effect in SLE, as suggested by Su et al. ,24 is the modulation of cytokine expression (interleukin‐10 and interleukin‐12 and interferon‐γ) by MPA. Jiang et al.…”
Section: Discussionmentioning
confidence: 99%